Gas bubble sensitisation of a non-ideal explosive using different gases as hot spots - Miguel Araos; Italo Onederra (International Society of Explosives Engineers, 2026)
Most of the current explosives for mining blasting activities rely on voids to become sensitive to initiation, then detonating and finally, sustaining that detonation. The use of voids is known as hot spot sensitisation. Various forms of voids serve as hot spots – gas bubbles (predominantly in bulk explosives), glass (or plastic microballoons, for packaged products), or expanded polystyrene (bulk explosives). Gas bubble sensitisation uses the decomposition of sodium nitrite to produce nitrogen gas bubbles, which are dispersed throughout the bulk explosion. These gas bubbles, when hit by a shock wave (such as from a booster), compress and heat up, subsequently decomposing the explosive and releasing energy to sustain the detonation. It has been suggested that the use of different types of gases to create voids in non-ideal explosives could offer some alternatives to the sensitisation process, which could be reflected in the change of the detonation properties of the explosive. The reason would be that each gas has a different ratio of specific heats (𝛾=𝐶𝑝/𝐶𝑣), and when these gas bubbles are compressed, they will heat up to different temperature, affecting the decomposition of the explosive and thus, the VOD.